Histophotometric complex for quantitative estimation of Insulin and Zinc Content in Pancreatic B-cells - Meyramov, G.G.; Kohnert, K.-D.; Korchin, V.I.; Tusupbekova, G.T.; Shaybek, A.S.; Abdraimova-Meyramova, A.G. (Fundamental and Experimental Biology, 2020)
It is presented a developed and constructed histophotometric complex for quantitative evaluation in relative units of content of deposited insulin and zinc in insulin-producing B-cells of histologic preparations of pancreas. The method previously used in similar studies was based on a visual assessment of the results of coloring the preparations, or a more accurate quantitative one under the conditions of using universal complexes, including a microscope with built-in measuring devices (photometers), the disadvantage of which is, as a rule, a very high cost limiting the possibility of their use. In addition, such complexes, in connection with their universality, are not suitable for studies related to the study of the functional state ofpancreatic B cells using highly specific histochemical methods for detecting insulin. The authors aimed to develop and create a study-oriented histophotometric complex of zinc and insulin in B cells, created using inexpensive components, which would help make quantitative analysis significantly more accessible to researchers working in the field of experimental diabetology.